Non-aqueous electrolyte secondary battery
By non-uniformly distributing the porous material concentration in the electrode mixture layer to enhance adhesive penetration, the separator and electrode bonding in non-aqueous electrolyte secondary batteries achieve superior adhesive strength, addressing cost and efficiency challenges in existing technologies.
Patent Information
- Application Number
- JP2022500313
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-14
- Filing Date
- 2021-01-29
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2041-01-29
AI Technical Summary
Existing methods for bonding separators and electrodes in non-aqueous electrolyte secondary batteries using multiple types of polymers with different glass transition temperatures increase costs without effectively improving adhesive strength.
The concentration of porous material in the electrode mixture layer is non-uniformly distributed, increasing from the core towards the adhesive, allowing the adhesive to penetrate and anchor into the pores, enhancing the adhesive force without changing material composition.
This approach significantly improves the adhesive strength between the separator and electrode, achieving greater than three times the adhesive force compared to conventional methods, while maintaining cost-effectiveness.
Smart Images

Figure 0007603049000002 
Figure 0007603049000003 
Figure 0007603049000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a non-aqueous electrolyte secondary battery. [Background technology]
[0002] In recent years, the demand for secondary batteries has been increasing in various fields. In particular, lithium-ion secondary batteries, which are non-aqueous electrolyte secondary batteries using non-aqueous electrolytes, have attracted attention because of their high energy density. In this type of secondary battery, a flat electrode body, in which positive and negative plates are stacked in multiple layers with a separator between them, is inserted into an exterior body. In the positive plate, a positive electrode composite layer is provided on both sides of a positive electrode core body, and in the negative plate, a negative electrode composite layer is provided on both sides of a negative electrode core body. The positive electrode active material and the negative electrode active material each have a structure that allows the insertion and removal of lithium ions. The separator is a porous material that allows the permeation of lithium ions while preventing short circuits due to electrical contact between the positive and negative plates.
[0003] The positive and negative electrodes are electrically connected to the current collectors and inserted into the exterior body. The exterior body is sealed after the electrolyte is poured in. To prevent the electrode body from losing its shape due to the load during transportation, this secondary battery has an adhesive layer on the surface of the separator, and the positive and negative electrodes are bonded together by thermocompression.
[0004] Patent Document 1 discloses a method for producing an electrode / separator laminate, which has an objective of bonding the separator and the electrode with sufficient adhesive strength when producing the electrode / separator laminate by thermocompression bonding the separator with an adhesive layer and an electrode, and includes a step of laminating an adhesive layer-attached separator made of a porous polyolefin film having an adhesive layer on at least one side thereof and an electrode having an electrode active material layer containing an electrode active material and an electrode binder so that the adhesive layer and the electrode active material layer are in contact with each other, and thermocompression bonding the electrodes. The adhesive layer contains a particulate polymer A having a glass transition temperature of -50 to 5°C and a particulate polymer B having a glass transition temperature of 50 to 120°C, the adhesive layer has an average thickness of 0.2 to 1.0 μm, and the thermocompression bonding is performed at 50 to 100°C. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2014 / 081035 Summary of the Invention
[0006] In a configuration in which a plurality of types of particulate polymers having different glass transition temperatures are used in order to improve the adhesive strength between the separator and the electrodes, the cost increases accordingly.
[0007] The nonaqueous electrolyte secondary battery according to the present disclosure is a nonaqueous electrolyte secondary battery comprising: a separator having an adhesive on at least one side thereof; and an electrode having a core and an electrode mixture layer, the electrode mixture layer being in contact with the adhesive, wherein the electrode mixture layer has a porous body concentration in a thickness direction that increases from the core toward the adhesive.
[0008] In the nonaqueous electrolyte secondary battery according to the present disclosure, the concentration of the porous body in the electrode mixture layer is controlled so as to be not uniform in the thickness direction but to increase from the core toward the adhesive. That is, the concentration of the porous body is relatively high near the surface of the electrode mixture layer that contacts the adhesive of the separator. Therefore, by bonding the porous body and the adhesive in the thermocompression bonding process, the adhesive penetrates more into the pores of the porous body, and the anchor effect is exerted predominantly.
[0009] In one embodiment of the present disclosure, the electrode mixture layer has a ratio of the porous body within a range of 5 μm from the surface on the adhesive side of 50% or more.
[0010] In another embodiment of the present disclosure, the electrode mixture layer is a positive electrode mixture layer containing a positive electrode active material, and the porous body is a conductive material.
[0011] According to the present disclosure, the adhesive strength between the separator and the electrode can be improved without changing the material composition, such as by forming the adhesive from a plurality of types of polymers. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a configuration diagram of a nonaqueous electrolyte secondary battery according to an embodiment. [Figure 2A] FIG. 2A is an explanatory view of adhesion in a nonaqueous electrolyte secondary battery according to an embodiment. [Figure 2B] FIG. 2B is an explanatory diagram of adhesion in a conventional nonaqueous electrolyte secondary battery. [Diagram 3] FIG. 3 is a block diagram of a method for evaluating adhesive strength of a nonaqueous electrolyte secondary battery according to an embodiment. [Figure 4A] FIG. 4A is an explanatory diagram (part 1) of a method for evaluating adhesive strength of a nonaqueous electrolyte secondary battery according to an embodiment. [Figure 4B] FIG. 4B is an explanatory diagram (part 2) of the method for evaluating the adhesive strength of the nonaqueous electrolyte secondary battery according to the embodiment. [Figure 5A] FIG. 5A is a binary image explanatory diagram (part 1) of the nonaqueous electrolyte secondary battery of the embodiment. [Figure 5B] FIG. 5B is a binary image explanatory diagram (part 2) of the nonaqueous electrolyte secondary battery of the example. [Figure 6] FIG. 6 is an explanatory diagram of a method for evaluating the porous body concentration of the nonaqueous electrolyte secondary battery of the embodiment. [Figure 7] FIG. 7 is an explanatory diagram of a method for evaluating the porous body concentration of a nonaqueous electrolyte secondary battery of a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0014] First, an overview of a prismatic secondary battery will be described. A prismatic secondary battery according to an embodiment of the present disclosure (hereinafter simply referred to as a secondary battery) includes an electrode body, an electrolyte, an exterior body in which the electrode body and the electrolyte are housed, and a sealing plate to which a positive electrode terminal and a negative electrode terminal are attached and which closes an opening of the exterior body. The electrode body has a structure in which positive electrodes and negative electrodes are alternately stacked with separators interposed therebetween. The exterior body is, for example, a flat, substantially rectangular parallelepiped-shaped metallic prismatic container with one end opened in the height direction. The exterior body and the sealing plate are, for example, made of a metallic material mainly composed of aluminum.
[0015] The electrolyte is preferably a non-aqueous electrolyte, and includes, for example, a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may be, for example, esters, ethers, nitriles, amides, or a mixture of two or more of these. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is replaced with a halogen atom such as fluorine. The electrolyte salt may be, for example, a lithium salt such as LiPF6.
[0016] A positive electrode terminal and a negative electrode terminal are attached to the sealing plate. The sealing plate has an elongated rectangular shape, with the positive electrode terminal disposed at one end in the longitudinal direction of the sealing plate and the negative electrode terminal disposed at the other end in the longitudinal direction of the sealing plate. The positive electrode terminal and the negative electrode terminal are external connection terminals that are electrically connected to other secondary batteries and loads, and are attached to the sealing plate via insulating members.
[0017] The positive electrode includes a positive electrode tab electrically connected to a positive electrode terminal, and the negative electrode includes a negative electrode tab electrically connected to a negative electrode terminal. The positive electrode terminal is electrically connected to a positive electrode tab group formed by stacking a plurality of positive electrode tabs via a positive electrode current collector, and the negative electrode terminal is electrically connected to a negative electrode tab group formed by stacking a plurality of negative electrode tabs via a negative electrode current collector. In addition, the sealing plate is provided with a liquid injection part for injecting a nonaqueous electrolyte and a gas exhaust valve for opening and discharging gas when an abnormality occurs in the battery.
[0018] The electrode body is divided, for example, into a first electrode group and a second electrode group. These electrode groups have the same laminated structure and dimensions, and are arranged in a laminated manner in the thickness direction of the electrode body. A positive electrode tab group consisting of multiple positive electrode tabs and a negative electrode tab group consisting of multiple negative electrode tabs are formed at the upper end of each electrode group, and are connected to each current collector plate of the sealing plate. The outer peripheral surfaces of these electrode groups are covered with a separator, and are configured so that independent battery reactions occur in these electrode groups.
[0019] The electrode body includes a plurality of positive electrodes and a plurality of negative electrodes. For example, the electrode group constituting the electrode body includes one more negative electrode than the positive electrode, and the negative electrodes are arranged on both sides of the electrode group in the thickness direction. A separator is arranged between each of the positive and negative electrodes, but each of the electrode groups may include only one separator. Each of the electrode groups includes an adhesive layer and is produced using a thermocompression process. More specifically, each of the electrode groups is produced by pressing a laminate in the stacking direction, in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked one by one with separators interposed therebetween, using a pair of hot plates to apply heat and pressure to the laminate, and bringing at least a part of the adhesive layer into a state where it exhibits adhesive force.
[0020] The positive electrode has a positive electrode core and a positive electrode composite layer provided on the surface of the positive electrode core. For the positive electrode core, a foil of a metal such as aluminum or an aluminum alloy that is stable in the potential range of the positive electrode, or a film with the metal disposed on the surface layer, can be used. The positive electrode composite layer contains a positive electrode active material, a conductive material, and a binder, and is preferably provided on both sides of the positive electrode core. The positive electrode can be produced, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a conductive material, and a binder, and then drying the coating, and compressing it to form a positive electrode composite layer on both sides of the positive electrode core.
[0021] The positive electrode has a structure in which a positive electrode composite layer made of a positive electrode composite is disposed on the entire surface of the positive electrode core except for the positive electrode tab (hereinafter referred to as the "base"). The thickness of the positive electrode core is, for example, 5 μm to 20 μm, and preferably 8 μm to 15 μm. The base of the positive electrode core has a rectangular shape when viewed from the front, and the positive electrode tab protrudes from one side of the rectangle. In general, a positive electrode core in which the base and the positive electrode tab are integrally formed is obtained by processing a single sheet of metal foil.
[0022] A lithium transition metal composite oxide is used as the positive electrode active material. Metal elements contained in the lithium transition metal composite oxide include Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, W, etc. Among them, it is preferable to contain at least one of Ni, Co, and Mn. Examples of suitable composite oxides include lithium transition metal composite oxides containing Ni, Co, and Mn, and lithium transition metal composite oxides containing Ni, Co, and Al.
[0023] Examples of the conductive material contained in the positive electrode mixture layer include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, and polyolefin resins. These resins may also be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or its salts, and polyethylene oxide (PEO).
[0024] The negative electrode has a negative electrode core and a negative electrode composite layer formed on the surface of the negative electrode core and composed of a negative electrode composite. For the negative electrode core, a foil of a metal such as copper that is stable in the potential range of the negative electrode, or a film with the metal disposed on the surface layer, can be used. The negative electrode composite layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core. The negative electrode can be produced, for example, by applying a negative electrode composite slurry containing a negative electrode active material and a binder to the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode composite layer on both sides of the negative electrode core.
[0025] The negative electrode has a structure in which a negative electrode composite layer is formed over the entire area of the base, which is the surface of the negative electrode core except for the negative electrode tab. The thickness of the negative electrode core is, for example, 3 μm to 15 μm, and preferably 5 μm to 10 μm. As in the case of the positive electrode, the base of the negative electrode core has a rectangular shape when viewed from the front, and the negative electrode tab protrudes from one side of the rectangle. In general, a negative electrode core in which the base and the negative electrode tab are integrally formed is obtained by processing a single sheet of metal foil.
[0026] As the negative electrode active material, for example, a carbon-based active material that reversibly absorbs and releases lithium ions is used. Suitable carbon-based active materials include natural graphite such as flake graphite, lump graphite, and earthy graphite, and artificial graphite such as lump artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). In addition, as the negative electrode active material, a Si-based active material composed of at least one of Si and a Si-containing compound may be used, or a carbon-based active material and a Si-based active material may be used in combination.
[0027] The binder contained in the negative electrode mixture layer may be fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., as in the case of the positive electrode, but it is preferable to use styrene-butadiene rubber (SBR). In addition, it is preferable that the negative electrode mixture layer further contains CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), etc. Among them, it is preferable to use SBR in combination with CMC or a salt thereof, and PAA or a salt thereof.
[0028] The outline of the prismatic secondary battery has been described above. Next, the structure of the electrode group and the separator in this embodiment will be further described.
[0029] FIG. 1 is an enlarged schematic cross-sectional view of the electrode group cut along a plane substantially perpendicular to the height direction in the stacking direction, and includes a part of a separator, a part of a positive electrode, and an adhesive layer.
[0030] As shown in Fig. 1, the separator 20 has a substrate and further has an adhesive 18 on at least one side, preferably both sides (for convenience of explanation, the figure shows a case where the adhesive 18 is on only one side). The substrate is made of a porous sheet having ion permeability and insulating properties. The separator 20 may be made of a porous substrate containing at least one selected from, for example, polyolefin, polyvinylidene fluoride, polytetrafluoroethylene, polyimide, polyamide, polyamideimide, polyethersulfone, polyetherimide, and aramid as a main component, and is preferably made of polyolefin, and particularly preferably made of polyethylene and polypropylene.
[0031] The adhesive 18 is formed by arranging multiple dots of adhesive (dot-shaped portions) by coating or other processing on at least one of the entire surfaces of one side surface of the separator 20 and the entire surface of the other side surface so that the area density is approximately constant.
[0032] The adhesive 18 may be applied over the entire surface of the separator instead of in dots. That is, the adhesive 18 may be arranged over at least one of the entire surface of one side surface and the entire surface of the other side surface of the separator so that the area density is substantially constant, and an adhesive layer may be provided on at least one side surface of the separator. The adhesive 18 may be a known material, such as an acrylic resin adhesive, a urethane resin adhesive, an ethylene-vinyl acetate resin adhesive, or an epoxy resin adhesive.
[0033] After forming a laminate by alternately stacking the positive and negative electrodes with the separator 20 interposed therebetween so that one side of the separator 20 on which the adhesive 18 is arranged faces the positive electrode, pressure and heat are applied to the laminate from both sides in the stacking direction by hot plates arranged on one side and the other side in the stacking direction, thereby softening a part of the adhesive. In this way, the separator 20 and the positive electrode are bonded with the adhesive, and the separator 20 and the negative electrode are bonded with the adhesive, thereby preventing the positive electrode, the negative electrode, and the separator 20 from being misaligned and causing a short circuit. In addition, a heat-resistant layer is arranged on either the positive electrode, the negative electrode, or the separator in order to prevent a short circuit between the positive electrode and the negative electrode. The heat-resistant layer contains inorganic particles such as aluminum oxide, and is composed of, for example, a ceramic heat-resistant layer.
[0034] As shown in FIG. 1, the positive electrode has a positive electrode core 10 and a positive electrode composite layer 12 provided on the surface of the positive electrode core 10. The positive electrode composite layer 12 contains a positive electrode active material, a conductive material, and a binder, and can be produced, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a conductive material, and a binder, etc., onto the positive electrode core 10, drying the coating, and then compressing it to form the positive electrode composite layer 12 on the surface of the positive electrode core 10. The positive electrode composite layer 12 of this embodiment is composed of a layer 14 having a relatively low porous body concentration and a layer 16 having a relatively high porous body concentration. In other words, the porous body concentration of the positive electrode composite layer 12 is not uniform but non-uniform in the thickness direction, and is configured so that the porous body concentration increases from the positive electrode core 10 toward the adhesive 18, and conversely, is configured so that the porous body concentration decreases from the adhesive 18 toward the positive electrode core 10. 1, non-porous body 13 is shown diagrammatically by a black circle, and porous body 15 is shown by a hatched circle. It can be said that in positive electrode mixture layer 12, the concentration of porous body 15 is relatively high on the adhesive 18 side, and the concentration of non-porous body 13 is relatively high on the positive electrode core 10 side. Alternatively, it can be said that in positive electrode mixture layer 12, the porous body is unevenly distributed on the adhesive 18 side.
[0035] As described above, the positive electrode mixture layer 12 includes a positive electrode active material, a conductive material, and a binder, and a lithium transition metal composite oxide is used as the positive electrode active material. Examples of the conductive material include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, and polyolefin resins. Among these, acetylene black is a typical example of a porous body. Therefore, as an example, the concentration of acetylene black as a conductive material contained in the positive electrode mixture layer 12 is made non-uniform in the thickness direction, and the concentration of acetylene black is increased from the positive electrode core 10 to the adhesive 18, so that the porous body concentration increases from the positive electrode core 10 to the adhesive 18.
[0036] 2A is a schematic diagram showing a state in which the positive electrode and separator 20 are joined in this embodiment. When positive electrode mixture layer 12 and adhesive 18 are in contact with each other and pressure and heat are applied to the laminate in this state from both sides in the stacking direction, adhesive 18 softens and penetrates into the pores of porous body 15, thereby exerting a dominant anchor effect and improving the adhesive strength between the positive electrode and separator 20.
[0037] 2B shows a schematic diagram of a conventional bonded state between a positive electrode and a separator 20 in which the porous body concentration of the positive electrode mixture layer 12 is uniform in the thickness direction. When the positive electrode mixture layer 12 and the adhesive 18 are in contact with each other and pressure and heat are applied to the laminate from both sides in the stacking direction in this state, the adhesive 18 softens, but the softened adhesive 18 has difficulty penetrating the pores of the porous body 15 (in other words, the non-porous body 13 inhibits the anchoring effect of the porous body 15), and the anchoring effect is not dominantly expressed. The adhesive strength is positively correlated with the porous body concentration on the surface side of the positive electrode mixture layer 12 that is in contact with the adhesive 18, and the adhesive strength increases as the porous body concentration increases.
[0038] The above is about the adhesive strength between the positive electrode and the separator 20, but the adhesive strength between the negative electrode and the separator 20 is similar. That is, the concentration of the porous body contained in the negative electrode mixture layer is made non-uniform in the thickness direction, and the concentration of the porous body is increased from the negative electrode core toward the adhesive 18. When pressure and heat are applied to the laminate in this state from both sides in the stacking direction, the adhesive 18 is softened, and the softened adhesive 18 penetrates into the pores of the porous body, and the anchor effect is dominantly exerted, improving the adhesive strength between the negative electrode and the separator 20. Therefore, it is sufficient to configure at least one of the positive electrode and the negative electrode so that the porous body concentration in the thickness direction of the electrode mixture layer increases from the electrode core toward the adhesive.
[0039] Examples will be described below.
[0040] <Example> FIG. 3 shows a method for evaluating adhesive strength in this example.
[0041] First, the separator 20 and the positive electrode 30 are prepared. The separator 20 has a heat-resistant layer 32 and further has an adhesive 18. The adhesive 18 is formed by disposing a plurality of dot-shaped adhesives 18 by processing such as coating so that the area density is approximately constant over the entire area of one side surface of the separator 20 on which the heat-resistant layer 32 is provided. The positive electrode 30 has a positive electrode composite layer. The adhesive 18 of the separator 20 and the positive electrode composite layer of the positive electrode 30 are brought into contact with each other, and the separator 20 and the positive electrode 30 are pressed using a pair of hot plates under predetermined conditions to apply heat and pressure, so that the adhesive 18 is in a state in which it exerts its adhesive force. After cooling, the separator 20 is peeled off, and the heat-resistant layer 32 is transferred to the positive electrode composite layer of the positive electrode 30. The adhesive force between the heat-resistant layer 32 of the separator 20 and the substrate is weaker than the adhesive force between the positive electrode 30 and the adhesive. Therefore, when the separator 20 is peeled off from the positive electrode 30, the bonded portion bonded by the adhesive 18 does not peel off from the positive electrode 30 and the heat-resistant layer 32, and the heat-resistant layer 32 peels off from the substrate.
[0042] 4A is a schematic diagram showing a state in which the heat-resistant layer 32 is transferred to the positive electrode mixture layer of the positive electrode 30. The adhesive 18 and the heat-resistant layer 32 are transferred in a dot pattern to the positive electrode mixture layer of the positive electrode 30. If the adhesive strength of the adhesive 18 is relatively large, the heat-resistant layer 32 is transferred, but if the adhesive strength of the adhesive 18 is relatively small, the heat-resistant layer 32 is not transferred. Therefore, the adhesive strength can be quantitatively evaluated by evaluating the number of transferred heat-resistant layers 32 or the concentration of the transferred heat-resistant layers 32.
[0043] Fig. 4B is a schematic diagram showing an image obtained by peeling the separator 20 off the positive electrode 30, photographing the surface of the positive electrode 30 from which the separator 20 has been peeled off with a camera, scanner, or the like, and binarizing the photographed image. In Fig. 4B, black indicates the positive electrode composite layer, and white dots indicate the transferred heat-resistant layer 32, i.e., the transfer marks. In such a binarized image, Transferred area density = (white area) / (black area) The transfer mark density is calculated by the above method to quantitatively evaluate the adhesive strength between the separator 20 and the positive electrode 30. When the separator 20 and the positive electrode 30 are pressed using a pair of hot plates under predetermined conditions, it is assumed that the adhesive strength between the heat-resistant layer 32 and the adhesive 18 is the same if the predetermined conditions are the same.
[0044] The present embodiment will now be described in more detail.
[0045] <Preparation of positive electrode> A positive electrode composite layer was formed on both sides of an aluminum foil having a thickness of 13 μm. The thickness of the positive electrode composite layer was 60 μm on one side after compression treatment. The length in the short direction of the positive electrode plate was 80 mm. The width (length in the short direction) of the current collecting tab part where the positive electrode core was exposed was 20 mm. The length in the long direction of the positive electrode plate was 140 mm. The positive electrode composite layer contained lithium nickel cobalt manganese composite oxide as a positive electrode active material, acetylene black as a conductive material, and polyvinylidene fluoride (PVDF) as a binder in a mass ratio of 97:2:1.
[0046] At this time, the positive electrode can be produced by applying a positive electrode composite slurry containing a positive electrode active material, a conductive material, and a binder, etc., onto a positive electrode core, drying the coating, and then compressing it to form a positive electrode composite layer on the positive electrode core. By changing the drying speed when drying the coating, the distribution of acetylene black as a conductive material was changed in the thickness direction, and the porous body concentration was changed in the thickness direction. Specifically, a conventional positive electrode with a substantially uniform porous body concentration was produced by drying at the same drying speed as in the conventional method, and a positive electrode of the embodiment in which the porous body concentration was non-uniform in the thickness direction by increasing the drying speed more than in the conventional method, and acetylene black as a conductive material was relatively unevenly distributed on the positive electrode surface was produced. By controlling the drying speed (water evaporation speed) when drying the positive electrode active material layer slurry, the concentration distribution of the conductive material in the positive electrode composite layer was changed, and the faster the drying speed, the greater the amount of conductive material contained in the region close to the surface of the positive electrode composite layer.
[0047] More specifically, the positive electrode mixture slurry containing the positive electrode active material, conductive material, and binder was dried under conditions such that the accumulated temperature received by the plate when passing through the entire drying process was approximately 265°C min., when the drying conditions for the positive electrode mixture slurry containing the positive electrode active material, conductive material, and binder were set to 25°C as the reference temperature and the temperature difference in the furnace temperature during the drying process was multiplied by the time (min.) required for the plate to pass through the furnace to calculate the accumulated temperature. As will be described later, the proportion of the porous body in the surface layer of the positive electrode plate within a range of 5 μm was 63.7%, which is more than 50%.
[0048] Similarly, a conventional positive plate was prepared as a comparative example by drying the positive electrode mixture slurry containing the positive electrode active material, conductive material, and binder under conditions where the cumulative temperature was calculated by multiplying the time (min.) required for the plate to pass through the furnace by the temperature difference in the drying process with a reference temperature of 25°C as the drying condition when the positive electrode mixture slurry was applied, and the cumulative temperature was about 170°C min. As described later, the proportion of the porous body in the surface layer of 5 μm of this positive electrode plate was 10.8%, which is less than 50%.
[0049] In summary, the materials of the electrode mixture layer in the examples and the comparative examples are the same, and the drying speed of the positive electrode mixture slurry is Example: approx. 265℃·min. Comparative example: approx. 170°C·min. It was changed to:
[0050] <separator> The separator used was made by coating one side of a single-layer polyethylene substrate with a ceramic heat-resistant layer, and applying an adhesive layer made of acrylic resin in dots on both sides of the ceramic heat-resistant layer. The thickness of the substrate layer of the separator was 12 μm, the thickness of the heat-resistant layer was 4 μm, and the width was 80 mm. The amount of adhesive in each dot was made to be approximately the same. The number density of the adhesive dots was also made to be approximately constant on one side of the separator.
[0051] <Thermocompression bonding process> The processing conditions for thermocompression bonding of the separator 20 and the positive electrode 30 were changed as follows for the sample using the positive electrode of the embodiment and the sample using the conventional positive electrode. (1)74 degrees, 20kN, 25 seconds (2)74 degrees, 25kN, 15 seconds (3)74 degrees, 25kN, 20 seconds (4)74 degrees, 25kN, 25 seconds (5)74 degrees, 30kN, 15 seconds <Adhesion strength evaluation> For each of the examples and conventional samples that were thermocompression bonded under the thermocompression bonding conditions (1) to (5) above, after sufficient cooling after thermocompression bonding, the separator 20 was peeled off from the positive electrode 30, and the surface of the positive electrode 30 was photographed with a scanner to obtain an image, which was then binarized to obtain a binary image. The transfer mark density in the binary image was measured. Transferred area density = (white area) / (black area) The white area is the area where the heat-resistant layer was transferred, and the black area is the total area of the electrode plate. The above formula is: Transfer mark density = (heat-resistant layer transfer area) / (total electrode plate area) This can be expressed as:
[0052] Fig. 5A is an example of a binarized image of the sample of the embodiment. Fig. 5B is an example of a binarized image of the conventional sample. In the sample of the embodiment, the concentration of the conductive material on the surface of the positive electrode 30 is relatively high, and the concentration of the porous body is high, so that the white area is relatively larger than that of the conventional sample.
[0053] Table 1 shows the results of evaluating the adhesive strength when the examples and the conventional samples were subjected to thermocompression bonding under five conditions (1) to (5).
[0054] [Table 1]
[0055] In Table 1, for example, when thermocompression was performed at 74 degrees, 20 kN, and 25 seconds, the transfer mark concentration of the sample of the embodiment was 4,962 ppm, or 0.4962%, and the transfer mark concentration of the conventional sample was 3,037 ppm, or 0.3037%. Therefore, the ratio of the adhesive strength of the sample of the embodiment to the conventional sample was 163%.
[0056] Similarly, when the sample was thermocompressed at 74 degrees, 25 kN, and 15 seconds, the transfer mark concentration of the sample of the embodiment was 2,662 ppm, i.e., 0.2662%, and the transfer mark concentration of the conventional sample was 1,415 ppm, i.e., 0.1415%. Therefore, the ratio of the adhesive strength of the sample of the embodiment to the conventional sample was 188%. Furthermore, when the sample was thermocompressed at 74 degrees, 25 kN, and 20 seconds, the transfer mark concentration of the sample of the embodiment was 5,629 ppm, i.e., 0.5629%, and the transfer mark concentration of the conventional sample was 5,381 ppm, i.e., 0.5381%. Therefore, the ratio of the adhesive strength of the sample of the embodiment to the conventional sample was 105%. Moreover, when the sample was thermocompressed at 74 degrees, 25 kN, and 25 seconds, the transfer mark concentration of the sample of the embodiment was 20,014 ppm, i.e., 2.014%, and the transfer mark concentration of the conventional sample was 12,596 ppm, i.e., 1.2596%. Therefore, the ratio of the adhesive strength of the sample of the embodiment to the conventional sample was 159%. Furthermore, when the sample was thermocompressed at 74 degrees, 30 kN, and 15 seconds, the transfer mark concentration of the sample of the embodiment was 12,010 ppm, i.e., 1.2010%, and the transfer mark concentration of the conventional sample was 3,430 ppm, i.e., 0.3430%. Therefore, the ratio of the adhesive strength of the sample of the embodiment to the conventional sample was 350%.
[0057] From these results, it was confirmed that the adhesive strength of the sample of the embodiment was greater than that of the conventional sample under all thermocompression bonding conditions. In particular, it was confirmed that the adhesive strength of the sample of the embodiment was significantly increased by more than three times under the thermocompression bonding conditions of 74 degrees, 30 kN, and 15 seconds.
[0058] Next, EDX (energy dispersive X-ray spectrometer) mapping of the positive electrode cross section was performed for the sample of the embodiment and the conventional sample. The electrode plate prepared by an ion milling device or the like was cut in the electrode plate thickness direction, and a cross-sectional image was taken using an SEM device at an acceleration voltage of 3 kV to obtain a cross-sectional SEM image. Carbon mapping was then performed by EDX to obtain the thickness direction distribution of the porous body.
[0059] In the EDX mapping image 304 of the example sample shown in Fig. 6, the porous material and the non-porous material are color-coded and then binarized. The concentration of the conductive material, acetylene black, is non-uniform in the thickness direction, and the concentration of the conductive material is relatively high on the surface of the positive electrode.
[0060] In addition, in the EDX mapping image 314 of the conventional sample shown in Fig. 7, the porous and non-porous substances are color-coded and then binarized, as in Fig. 6. The concentration of acetylene black, which is a conductive material, is approximately uniform in the thickness direction, and the concentration on the positive electrode surface is relatively low compared to the sample of the embodiment.
[0061] Furthermore, in order to quantitatively evaluate the concentration of the conductive material on the positive electrode surface of both samples, i.e., the concentration of the porous body, the proportion of the conductive material on the positive electrode surface, more specifically within a 5 μm range from the surface of the positive electrode mixture layer, was counted.
[0062] The conductive material concentration in the range of 5 μm from the surface of the positive electrode mixture layer, i.e., the porous body concentration, was calculated as the ratio of the white area to the black area in the binarized image, similar to the above-mentioned transfer mark concentration. Porous body concentration = (white area) / (black area) As a result, Example sample = 63.7% Traditional sample = 10.8% It should be noted that the transfer mark density in Table 1 is the density in a planar image of the positive electrode mixture layer, and the conductive material density in Fig. 6 and Fig. 7 is the density in an image in the thickness direction of the positive electrode mixture layer.
[0063] In order to allow the adhesive to penetrate into the pores of the porous body by adhering the porous body and the adhesive to exhibit an advantageous anchoring effect, it is desirable that as much of the porous body as possible be present within a range of about 5 μm, which is assumed to be the range in the thickness direction where the adhesive particles penetrate, and it is considered that the anchoring effect can be sufficiently exhibited if the porous body is 50% or more, which is a ratio that exceeds that of other materials in the positive electrode mixture layer. For this reason, when focusing on the range of 5 μm from the surface of the positive electrode mixture layer, the conductive material concentration, i.e., the porous body concentration, is preferably 50% or more, and more preferably 60% or more. [Explanation of symbols]
[0064] 10 Positive electrode core body 12 Positive electrode mixture layer 14 Layer with relatively low porous material concentration 16 Layer with relatively high concentration of porous media 18 Adhesive 20 Separator
Claims
1. A separator having an adhesive on at least one surface thereof; an electrode having a core body and an electrode mixture layer, the electrode mixture layer being in contact with the adhesive; wherein the electrode mixture layer has a porous body concentration in a thickness direction that increases from the core body toward the adhesive.
2. The electrode mixture layer has a porous body having a ratio of 50% or more within a range of 5 μm from the surface on the adhesive side. The nonaqueous electrolyte secondary battery according to claim 1 .
3. The electrode mixture layer is a positive electrode mixture layer containing a positive electrode active material, The porous body is a conductive material.
3. The nonaqueous electrolyte secondary battery according to claim 1.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP2010287472A
Nonaqueous electrolyte secondary battery
JP2017073328A
Positive electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2017084769A
Method for producing electrode / separator laminate, and lithium-ion rechargeable battery
WO2014081035A1
